Epidemiology of American Football Injuries at Universities in the United Kingdom - Bayram, John M. (Orthop J Sports Med, 2020)
BACKGROUND: College-level American football injury data are routinely collected; however, data relating to American football injuries at universities in the United Kingdom have never been reported. PURPOSE: To describe the epidemiology of UK university American football injuries. STUDY DESIGN: Descriptive epidemiology study. METHODS: An online survey tool was used to collect the injury data of 410 players from 56 UK university teams who participated in the 2014-2015 British Universities and College Sports American football season. Survey data were collected from January to February 2016 and were analyzed to determine the incidence and patterns of injury. RESULTS: Overall, 710 injuries and 204 concussions were self-reported among the 410 participants, of which 334 (81.5%) were injured and 131 (32.0%) experienced concussion symptoms. The rate of injury per 100 athlete-seasons was greater in defensive players (195.3) than offensive players (155.1). The most common injuries were knee and ankle ligament injuries. Most injuries were classified as severe (time loss of >4 weeks). CONCLUSION: UK university American football injuries differ markedly from those reported for US colleges. UK university players appear to have less playing experience, greater concussion risks, more severe injuries, and a greater proportion of injuries in defensive players versus offensive players.